2019
DOI: 10.1002/ab.21827
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect relationships among posttraumatic stress disorder, depression, hostility, anger, and verbal and physical aggression in returning veterans

Abstract: Hostility, anger, and aggression are conceptually related but unique constructs found to occur more often among veterans with PTSD than among civilians or veterans without PTSD. However, the pathways between PTSD, depression, hostility, anger, and aggression have not been comprehensively characterized. Therefore, drawing on a sample of returning Operation Enduring Freedom/Operation Iraqi Freedom combat veterans (N = 175; 95% male; mean age 30 years), this study sought to examine the direct and indirect relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
4
1
1
Order By: Relevance
“…Alternatively, it is possible that anger acted as a commonality between participants who felt they had been treated unjustly by their employers and as such became a bonding mechanism for group members. Finally, correlations between anger and PTSD symptoms (r = .16) were lower than in previous studies (Bhardwaj et al, 2018;Novaco et al, 2012) and lower than that reported in the meta-analysis of Orth and Wieland (2006). Thus, it is possible that some group participants were experiencing non-PTSD-related anger confined to other life domains, such as relationships and family, which may have not necessarily influenced their decision making about persisting with PTSD treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…Alternatively, it is possible that anger acted as a commonality between participants who felt they had been treated unjustly by their employers and as such became a bonding mechanism for group members. Finally, correlations between anger and PTSD symptoms (r = .16) were lower than in previous studies (Bhardwaj et al, 2018;Novaco et al, 2012) and lower than that reported in the meta-analysis of Orth and Wieland (2006). Thus, it is possible that some group participants were experiencing non-PTSD-related anger confined to other life domains, such as relationships and family, which may have not necessarily influenced their decision making about persisting with PTSD treatment.…”
Section: Discussioncontrasting
confidence: 63%
“…Research has also demonstrated that depression and suicidality are related to aggression [ 61 - 63 ]. Other research has even related to aggression [ 64 , 65 ] or focused on predicting personality disorder through aggression [ 66 - 68 ]. All these findings tend to question whether aggression has impacts on global health in the general population [ 69 - 71 ], which could open the way for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our subsample of veterans with a retrospective history of greater than minimal early life adversity, depression and anxiety symptoms were significantly associated with anger. Studies with post‐9/11 veterans have shown an indirect relationship between PTSD and anger through depressive symptoms (Angkaw et al, 2013; Bhardwaj et al, 2019), suggesting that although anger is a symptom of PTSD, depressive symptoms play an important role in anger. Notably, these studies relied on mediation methods that lacked control of confounders (Angkaw et al, 2013) or controlled only for basic demographics of age and gender (Bhardwaj et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with post‐9/11 veterans have shown an indirect relationship between PTSD and anger through depressive symptoms (Angkaw et al, 2013; Bhardwaj et al, 2019), suggesting that although anger is a symptom of PTSD, depressive symptoms play an important role in anger. Notably, these studies relied on mediation methods that lacked control of confounders (Angkaw et al, 2013) or controlled only for basic demographics of age and gender (Bhardwaj et al, 2019). Although our sample size did not allow us to explore the differential impact of early life adversity type and timing on the relationships among depression and anxiety with current anger, our findings align with relevant recent studies.…”
Section: Discussionmentioning
confidence: 99%